Discriminate Properties of Three Specific and Generic Health-Related Quality of Life Questionnaires in Heart Failure - M Asadi-Lari; A Rao; D Gray (Tehran University of Medical Sciences, 2005)
Objectives: To assess health-related quality of life (HRQL) in patients with suspected heart failure (HF) and to explore discriminate properties of the tools, two generic questionnaires, Short Form 36 (SF-36) and EuroQol 5D (EQ-5D) and one specific, the Minnesota Living with Heart Failure questionnaire (MLHF-Q) HRQL were employed and compared with New York Heart Association (NYHA) functional class. Method: All patients with symptoms suggestive of heart failure referred to University Hospital, Nottingham, between June 2002 and March 2003. Confirmation of left ventricular systolic dysfunction carried out by echocardiography. Main Results: 223 patients (median age=74) were referred. HF was confirmed in 81. Lower HRQL scores were found in older patients (SF-36 and EQ-5D: P30 (P= ns; P<0.05; P= ns respectively). Among those with confirmed heart failure, lower mean scores were found in both subscales of SF-36, four of six subscales in EQ-5D and all MLHF-Q subscales, but these were not statistically significant. SF-36 Mental Component Score (MCS) and the emotional subscale of MLHF-Q were more sensitive to depressive disorders than EQ-5D ((P< 0.001; p<0.001; and P< 0.05 respectively). Regression analysis indicated that only SF-36 Physical Component Score (PCS) was able to differentiate significantly between NYHA functional classes (P< 0.01). The validity of MLHF-Q was confirmed by correlation with various subclasses in other HRQL measures (P< 0.001) and known group analysis with NYHA functional class (P< 0.001 in both physical and emotional subscales). Conclusion: The specific HRQL measure, MLHF-Q, was more sensitive to functional status in heart failure but emotional abnormalities and general affections were more readily identified by generic tools. Employing both generic and specific HRQL instruments seems necessary in suspected and confirmed heart failure. MLHF-Q showed appropriate construct validity in this sample.